Investigating the spatial distribution and effects of nearshore topography on Acropora cervicornis abundance in Southeast Florida - Nicole L. D’Antonio; David S. Gilliam; Brian K. Walker (PeerJ, 2016)
Dense Acropora cervicornis aggregations, or patches, have been documented within nearshore habitats in Southeast Florida (SE FL) despite close proximity to numerous anthropogenic stressors and subjection to frequent natural disturbance events. Limited information has been published concerning the distribution and abundance of A. cervicornis outside of these known dense patches. The first goal of this study was to conduct a spatially extensive and inclusive survey (9.78 km2) to determine whether A. cervicornis distribution in the nearshore habitat of SE FL was spatially uniform or clustered. The second goal was to investigate potential relationships between broad-scale seafloor topography and A. cervicornis abundance using high resolution bathymetric data. Acropora cervicornis was distributed throughout the study area, and the Getis-Ord Gi* statistic and Anselin Local Moran’s I spatial cluster analysis showed significant clustering along topographic features termed ridge crests. Significant clustering was further supported by the inverse distance weighted surface model. Ordinal logistic regression indicated 1) as distance from a ridge increases, odds of reduced A. cervicornis abundance increases; 2) as topographic elevation increases, odds of increased abundance increases; and 3) as mean depth increases, odds of increased abundance increases. This study provides detailed information on A. cervicornis distribution and abundance at a regional scale and supports modeling its distributions in similar habitats elsewhere throughout the western Atlantic and Caribbean. Acropora cervicornis is frequently observed and in areas an abundant species within the nearshore habitat along the SE FL portion of the Florida Reef Tract (FRT). This study provides a better understanding of local habitat associations thus facilitating appropriate management of the nearshore environment and species conservation. The portion of the FRT between Hillsboro and Port Everglades inlets should be considered for increased management and protection to reduce local stressors.